Tác động kinh tế của chi tiêu công tại các quốc gia đang phát triển: Vai trò của cán cân ngân sách - Trần Trung , Kiên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This paper re-examines the impact of public expenditure on economic growth in developing countries, and the role of fiscal balance is particularly considered in this nexus. By using a panel covering 66 developing countries for the 1998–2016 period, the empirical results indicate the negative growth effect of public expenditure. Interestingly, the state of fiscal balance plays a significant role in explaining the growth effect of public expenditure. In particular, fiscal decifit is found to aggravate the negative growth effect of public expenditure.
Keywords: Public expenditure; Budget balance; Economic growth